HIV/AIDS National Strategic Plans of Sub-Saharan African countries: an analysis for gender equality and sex-disaggregated HIV targets. Issue 10 (31st August 2017) - Sherwood, Jennifer; Sharp, Alana; Cooper, Bergen; Roose-Snyder, Beirne; Blumenthal, Susan
Abstract: National Strategic Plans (NSPs) for HIV/AIDS are country planning documents that set priorities for programmes and services, including a set of targets to quantify progress toward national and international goals. The inclusion of sex-disaggregated targets and targets to combat gender inequality is important given the high disease burden among young women and adolescent girls in Sub-Saharan Africa, yet no comprehensive gender-focused analysis of NSP targets has been performed. This analysis quantitatively evaluates national HIV targets, included in NSPs from eighteen Sub-Saharan African countries, for sex-disaggregation. Additionally, NSP targets aimed at reducing gender-based inequality in health outcomes are compiled and inductively coded to report common themes. On average, in the eighteen countries included in this analysis, 31% of NSP targets include sex-disaggregation (range 0–92%). Three countries disaggregated a majority (>50%) of their targets by sex. Sex-disaggregation in data reporting was more common for targets related to the early phases of the HIV care continuum: 83% of countries included any sex-disaggregated targets for HIV prevention, 56% for testing and linkage to care, 22% for improving antiretroviral treatment coverage, and 11% for retention in treatment. The most common target to reduce gender inequality was to prevent gender-based violence (present in 50% of countries). Other commonly incorporated target areas related to improving women's access to family planning, human and legal rights, and decision-making power. The inclusion of sex-disaggregated targets in national planning is vital to ensure that programmes make progress for all population groups. Improving the availability and quality of indicators to measure gender inequality, as well as evaluating programme outcomes by sex, is critical to tracking this progress. This analysis reveals an urgent need to set specific and separate targets for men and women in order to achieve an equitable and effective HIV response and align government planning with international priorities for gender equality.